2005
DOI: 10.1002/0471140864.ps2008s39
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Methods for the Determination of Protein Interactions

Abstract: This unit provides guidelines on how to use steady-state fluorescence spectroscopy for the quantification of protein-protein interactions. The fluorescence of a protein is characterized by its excitation and emission spectra, quantum yield, and anisotropy. These parameters can change upon interaction with another protein and can be used to measure the extent of complex formation. The source of fluorescence can be an intrinsic fluorophore, such as tryptophan or tyrosine; a covalently attached fluorescent dye; o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…F A and F AS represent the fluorescence signal of free protein A (UBM2) and the complex AS (UBM2⅐Ub), respectively, C A is the total concentration of UBM2, C S is the total concentration of the substrate S (Ub), and p is the stoichiometry value (28).…”
Section: Methodsmentioning
confidence: 99%
“…F A and F AS represent the fluorescence signal of free protein A (UBM2) and the complex AS (UBM2⅐Ub), respectively, C A is the total concentration of UBM2, C S is the total concentration of the substrate S (Ub), and p is the stoichiometry value (28).…”
Section: Methodsmentioning
confidence: 99%
“…HSA is a single chain protein that contains one tryptophan residue (Trp214). Since the emission of this aminoacid is very sensitive to changes in its microenvironment, its fluorescence can be used as a signal for monitoring interactions [14]. So, in binding assays the fluorescence intensities of HSA were determined by monitoring the changes in fluorescence intensities from Trp214.…”
Section: Determination Of Binding Parametersmentioning
confidence: 99%
“…Various spectroscopic methods, also based on fluorescence emission, have been developed for studying protein-protein interactions (for details see Groemping and Hellmann [20]). Using fluorescence microscopy, Demeule et al [21] have shown how protein aggregates can be detected and char-acterised.…”
Section: Research Articlementioning
confidence: 99%